2005
DOI: 10.1038/nature04407
|View full text |Cite
|
Sign up to set email alerts
|

A var gene promoter controls allelic exclusion of virulence genes in Plasmodium falciparum malaria

Abstract: Mono-allelic expression of gene families is used by many organisms to mediate phenotypic variation of surface proteins. In the apicomplexan parasite Plasmodium falciparum, responsible for the severe form of malaria in humans, this is exemplified by antigenic variation of the highly polymorphic P. falciparum erythrocyte membrane protein 1 (PfEMP1). PfEMP1, encoded by the 60-member var gene family, represents a major virulence factor due to its central role in immune evasion and intravascular parasite sequestrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
353
4
4

Year Published

2006
2006
2019
2019

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 256 publications
(375 citation statements)
references
References 29 publications
14
353
4
4
Order By: Relevance
“…Yet, the intron sequences apparently do harbor an insulator activity that antagonizes spreading of chromatin activation into neighboring loci (48). This agrees with previous results, suggesting that the upsCpromoter-intron interaction has a boundary function to protect var genes in chromosome-central clusters from activation through nearby euchromatic regions and neighboring var genes (49).…”
Section: Cis-regulatory Elements That Control Var Expressionsupporting
confidence: 81%
See 1 more Smart Citation
“…Yet, the intron sequences apparently do harbor an insulator activity that antagonizes spreading of chromatin activation into neighboring loci (48). This agrees with previous results, suggesting that the upsCpromoter-intron interaction has a boundary function to protect var genes in chromosome-central clusters from activation through nearby euchromatic regions and neighboring var genes (49).…”
Section: Cis-regulatory Elements That Control Var Expressionsupporting
confidence: 81%
“…Importantly, it was shown that a single active var promoter is sufficient to silence endogenous var genes and to ensure mutually exclusive expression of a single var gene (48,50). Together, it is reasonable to suggest that interplay between the promoter and intronic cis-regulatory elements generates a stably inherited silenced chromatin environment.…”
Section: Cis-regulatory Elements That Control Var Expressionmentioning
confidence: 99%
“…In turn, exposure on the erythrocyte surface triggers antibody-dependent immune responses in which semi-immunity of exposed individuals is rooted. In a typical "arms race" the parasite circumvents elimination by the immune system through antigenic variation, exclusively expressing one of many PfEMP1 variants at any specific time point (17). Thus, again, export and trafficking of proteins into the host cell cytosol are key for parasite survival, chronic infections, and pathology of malaria.…”
Section: Remodeling To Make the Home Habitablementioning
confidence: 99%
“…Thus the var promoter is sufficient for both the silencing and the monoclinic transcription of a PfEMPI allele. [ 96 ] 33. Summary…”
Section: Possible Receptors Identified By In Vitro Binding Assaysmentioning
confidence: 99%